Lost and Found: Decline and Reemergence of Non-Native Vowel Discrimination in the First Year of Life. Issue 1 (2nd January 2019) - de Klerk, Maartje; de Bree, Elise; Kerkhoff, Annemarie; Wijnen, Frank
ABSTRACT: Our aim was to investigate perceptual attunement (PA) in vowel perception of Dutch-learning infants (6-8-10-month-olds) using the hybrid visual fixation paradigm (Houston et al., 2007). Infants were habituated to one phoneme and subsequently tested on items in which a token of the habituated phoneme alternated with either another token of the same phoneme, or a token from another phonemic category. Habituation involved tokens of multiple speakers. Infants were tested on a native (/aː/-/eː/) and non-native (/ɛ/-/æ/) contrast. The 6-month-olds ( n  = 38), 8-month-olds ( n  = 44) and 10-month-olds ( n  = 35) discriminated the native contrast. The non-native contrast was discriminated by the group of 6-month-olds ( n  = 42) but not the 8-month-olds ( n  = 47), in line with PA. However, the 10-month-olds ( n  = 39) also showed discrimination. We conclude that discrimination of phonetic categories can occur after perceptual attunement; discrimination performance is sensitive to tasks applied.